Low emission zones improve air quality and health but temporarily decrease life satisfaction - Luis Sarmiento; Nicole Wägner; Aleksandar Zaklan (DIW Weekly Report, 2022)
Air pollution results in high economic costs arising from its negative impacts on human health, especially in urban areas. Driving restriction policies such as low emission zones (LEZs) are designed to improve air quality. Indeed, empirical analyses in this Weekly Report confirm that LEZs reduce traffic-related air pollution. However, the analyses also reveal unintended adverse effects on secondary contaminants like ozone and on air pollution in adjacent areas. New evidence based on data from the Socio-Economic Panel (SOEP) shows that LEZs temporarily decrease their residents' life satisfaction despite positive health impacts. The magnitude of the decline depends on personal life circumstances: For example, there are stronger adverse effects on life satisfaction of diesel vehicle owners and people younger than 65. The results of this study suggest that mobility restrictions and the associated adjustment costs reduce policy acceptance. More effectively communicating the health advantages of LEZs to the population or utilizing transfer mechanisms such as public transport vouchers could mitigate these effects.
Keywords: Q53; Q58; I31; I18; 330; low emission zones; air quality; well-being; health; difference-in-differences